Preparing the quality of financial statements at health centers: to explore the role of regional inspectorates and professionalism of accounting personnel - Alwan Sri Kustono; Ardhya Yudistira Adi Nanggala (STIE Perbanas Surabaya, 2020)
This study aims to analyze the effect of professionalism and the inspectorates’ existence on the quality of health center financial statements in Situbondo Regency. This study uses a qualitative phenomenological approach because it deals with social phenomena as well as their interactions with certain environments and conditions. The informants were selected from health center’s accounting personnel. The data were collected using a focus group discussion. The results show that professionalism has an effect on the quality of financial statements because professional employees are skilled employees in the field and they can carry out their tasks seriously and responsibly, understand the rules, be objective and be oriented to quality results. The inspectorates’ existence encourages the health center to conduct financial reporting in accordance with the applicable standards due to the aspects of supervision and coaching.